Answer:
(2x-10)^2
Explanation:
Follow the process of completing the square to solve x^2 - 10x + 8 = 0
First we subtract 8 from both sides
x^2 - 10x = -8
In completing the square method we take half of coefficient of middle temr -10x and then we square it
-10/2 = -5
(-5)^2= 25
Now we add 25 on both sides
x^2 - 10x +25 = -8+ 25
x^2 - 10x +25 = 17
Now we factor the left hand side x^2 -10x+25
We take half of middle term -10/2
(x-10/2)^2 that is (2x-10)^2
So the left hand side of the equation factor is (2x-10)^2